The end of the wor(l)d as we know it? : language in postapocalyptic novels (2011)
In recent times, the idea of apocalypse has consumed the public consciousness. Naturally, this preoccupation with the end of the world has been a frequent subject for literary exploration. Cormac McCarthy’s The Road and Margaret Atwood’s Oryx and Crake are two recent novels that are set in the aftermath of global destruction. In The Road, an unnamed cataclysmic event has left the world in ruins, while in Oryx and Crake, the human race has been nearly annihilated by a man-made pandemic. As a result of these apocalyptic events, the postapocalyptic landscapes of the novels have been radically changed and rendered unspeakable for many of the characters that have survived. These characters are equipped only with the signifiers of the old world, and these signifiers no longer hold meaning in the new, postapocalyptic world. Therefore, as a result of the cataclysmic events, the postapocalyptic worlds of The Road and Oryx and Crake become sites for linguistic transformation. Both novels feature protagonists, in the father and Snowman, who represent the pre-apocalyptic world. These characters struggle to find their place in the new world, since they are burdened by the signifiers of the old world. Ultimately, their existences prove anachronistic, as they are unable to fully define themselves in the new world. Both novels also feature characters, in the boy and the Crakers, who represent the postapocalyptic world. These characters are charged with determining the linguistic transformation that will take place in the postapocalyptic world. Both the boy and the Crakers employ a simple, pared-down language that stands in stark contrast to the language of the pre-apocalyptic world. As a result of the apocalyptic events in the novels, language has been restored to its essential elements. Ultimately, both The Road and Oryx and Crake affirm language as a redemptive and inextricable part of human existence. They also suggest, however, that if language is to exist after an apocalyptic event, it must be radically re-imagined.